Hubungan Antara Upacara Tedak Siten dan Hukum dalam Masyarakat Jawa - NAJWA Az-Zahra (Universitas Ngudi Waluyo, 2025)
Customary law can serve as a reflection of a nation's or country's character, and even embody the spirit and soul of the relevant nation as an element of national identity. One example is the Tedhak Siten tradition. Tedhak Siten is a series of traditional rituals from the Javanese life cycle that is increasingly rare nowadays. The term 'Tedhak Siten' comes from 'Tedhak', which means 'to descend' (to step), and 'Siten' or 'Siti', which means 'earth', so Tedhak Siten is a tradition where a child steps on the ground for the first time. 1) It is therefore necessary to examine the meaning and function of the Tedhak Siten ceremony in the context of Javanese legal culture, and 2) the Tedhak Siten ceremony from the perspective of modern law, using the Descriptive Method and then the Resulst is. 1) The Tedhak Siten ceremony is not merely a cultural ritual, but also an integral part of Javanese customary legal culture that regulates both social and spiritual relationships in society. Its main functions are as a symbol of respect for nature, the development of a child's character, and the strengthening of binding social norms within the Javanese community while also serving as a cultural identity passed down through generations. 2) However, in modern times the ceremony is often overlooked as modern society tends to prioritize practicality, resulting in the Tedhak Siten tradition still being performed but with reduced materials, simpler procedures, and fewer ritual accessories. Abstrak Hukum adat ini dapat menjadi cerminan kepribadian suatu bangsa atau negara, bahkan mewadahi jiwa dan bangsa yang bersangkutan sebagai bagian dari unsur jati diri bangsa atau unsur identitas nasional. Salah satu contohnya adat atau Tradisi Tedhak Siten. Tedhak Siten merupakan rangkaian prosesi adat tradisi daur hidup masyarakat jawa yang mulai jarang dilaksanakan. Tedhak Siten berasal dari kata Tedhak berarti turun (menapakkan kaki) dan Siten atau Siti yang artinya tanah, sehingga Tedhak Siten merupakan tradisi menginjakkan atau menapakkan kaki ke tanah bagi seorang anak. 1) Maka perlu makna dan fungsi upacara Tedak Siten dalam konteks budaya hukum masyarakat Jawa serta 2) upacara Tedak Siten dalam perspektif hukum modern dengan menggunakan Metode Deskriptif lalu menghasilkan hasil 1) Upacara Tedak Siten bukan hanya ritual budaya, tetapi juga bagian integral dari budaya hukum adat Jawa yang mengatur hubungan sosial dan spiritual masyarakat. Fungsi utamanya adalah sebagai simbol penghormatan kepada alam, pembentukan karakter anak, dan penguatan norma sosial yang mengikat dalam komunitas Jawa, sekaligus menjadi identitas budaya yang diwariskan turun-temurun 2) hal ini dipandang sebelah mata karena masyarakat kaum modern hanya lebih mengarah kepada kepraktisan, sehingga budaya hukum tedak siten tetap dilakukan namun mengalami pengurangan dalam material, pelaksanaan upacara maupun perlengkapan upacara.